PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET PADA TEMA 7 PERKEMBANGAN TEKNOLOGI PRODUKSI PANGAN - Noor Laeli Salsabila; Yuyun Elizabeth Patras; Suci Siti Lathifah (STKIP Subang, 2023)
This study aims to determine the feasibility of Liveworksheet-based E-LKPD development products on theme 7 development of food production technology in grade III SDN 3 Nyangkowek. This type of research is research and development (R&D) using the ADDIE model, namely (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is a validation questionnaire sheet to determine product feasibility. The results of Liveworksheet-based E-LKPD development research on theme 7 of the development of food production technology developed obtained a level of validity from material experts of 100% with very feasible categories, linguists with very feasible categories of 100% and media experts with quite valid categories of 77%. Meanwhile, the student response questionnaire stated that E-LKPD is very practical by obtaining a percentage of practicality of 93.5%. Thus, it can be concluded that Liveworksheet-based E-LKPD on theme 7 of the development of food production technology in grade III SDN 3 Nyangkowek is declared feasible and can be used in the learning process.